2017
DOI: 10.1016/j.stemcr.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gata4 and Tbx5 by Nicotine-Mediated DNA Methylation in Myocardial Differentiation

Abstract: SummaryMaternal nicotine exposure causes alteration of gene expression and cardiovascular programming. The discovery of nicotine-medicated regulation in cardiogenesis is of major importance for the study of cardiac defects. The present study investigated the effect of nicotine on cardiac gene expression and epigenetic regulation during myocardial differentiation. Persistent nicotine exposure selectively inhibited expression of two cardiac genes, Tbx5 and Gata4, by promoter DNA hypermethylation. The nicotine-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
1
20
1
1
Order By: Relevance
“…GATA4 is well known for its central role in embryogenesis [7], and in myocardial differentiation and function [8]. Besides, this protein is thought to be necessary for testicular development [9].…”
Section: Introductionmentioning
confidence: 99%
“…GATA4 is well known for its central role in embryogenesis [7], and in myocardial differentiation and function [8]. Besides, this protein is thought to be necessary for testicular development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of any of the proteins or their interactions can result in atrial or ventricular septal defects . Another previous study showed that nicotine directly suppresses myocardial differentiation by regulating the expression of cardiac genes such as Gata4 and Tbx5 via promoter of DNA hypermethylation, thereby contributing to the cause of cardiac defect associated with smoking . Mutation of HAND1 has been shown to hinder the effects of GATA4, another vital cardiac transcription factor, and is associated with congenital heart disease .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the idea that early life, including early (in utero) exposure to environmental factors, such as nicotine, hormones, and nutrients, influences development, with long-lasting effects on organ and tissue function (a phenomenon called developmental programming (43,44)), also has major implications for our understanding of CVD development and progression. In mammals, DNA demethylation in the parental gametes occurs by both active demethylation by translocation (TET) proteins and passive loss of methylation during subsequent cell divisions (4).…”
Section: The Evidence For Transgenerational Epigenetic Inheritancementioning
confidence: 99%
“…Experiments in animals show that nicotinic stimulation of acetylcholine receptors inhibits myocardial differentiation by down-regulation of Tbx5 and Gata4 in both differentiating embryonic bodies and in the offspring’s heart, and this is accompanied by promoter hypermethylation (44). Physical exercise influences the DNA methylation profile of adipose tissue in apparently healthy individuals, including at a number of genes implicated in the development of type 2 diabetes (62).…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation